Comparative analysis of cascaded fuzzy-PI controllers based-MPPT and perturb and observe MPPT in a grid-connected PV system operating under different weather and loading conditions - Otmane, Harici; Mouloudi, Youssef; Mokhtar, Bendjebbar (Institute of Advanced Engineering and Science, 2019)
In this paper, a comparison is carried out between MPPT technique using a hybrid cascaded Fuzzy-PI Controller and Perturb and Observe (P&O) MPPT technique. The two techniques are compared in a system which consists of a photovoltaic system connected to a grid via a two-level three-phase inverter. The P&O and Fuzzy-PI techniques are examined under different weather conditions, namely, ramp change in irradiation level and ramp change in temperature levels. Disturbances represented by fluctuations in power demand from the utility grid is generated to assess the robustness of each of the two controllers. The Fuzzy-PI based MPPT, has proved its excellent tracking and robustness against abrupt perturbations. Simulations of the system performances using the two regulators are performed to validate the conceptual standings.